Internet et enjeux de pouvoir dans le champ universitaire ivoirien - Aghi Bahi; Gadou Dakouri (Communication)
By adopting the question of the stakes involved in domination as the principal angle of attack, this article examines the reasons that teachers and researchers at the University of Cocody, Ivory Coast, have to use the Internet. The results of this qualitative inquiry show that the Internet is used principally as a way around the deficiencies in socio-technical infrastructure. However, the elements of both personal ambition and the power plays which structure the logic in the university field in the Ivory Coast prevent the constitution of a real virtual space for intellectual exchange.